The Gambaran Pencegahan Cedera Jarum Suntik di Rumah Sakit pada Mahasiswa Profesi Ners Fakultas Keperawatan Universitas Riau - CINDIKIA PUTRI (Jurnal Medika Hutama, 2022)
Background: Needle stick injury is a major cause of occupational injury for healthcare workers, including nursing profession students. Purpose: This study aimed to provide description of needlestick injury prevention to nursing profession students. Method: This study used a simple descriptive design involving 110 nursing profession students by using a total sampling technique. The data was gathered using questionnaire. This study used univariate analysis Result: The study’s result showed that majority of nurse program was A program (77.3%), the majority of respondents were female, namely (85.5%) in A program and (60%) in B program. The result showed that (97.6%) were good enough on needle stick injury prevention in A program and (100%) in B program. The used of safety box as many as (67.1%) were good enough in A program and (56%) in B program. The applied of non recapping technique were good enough by (98.8%) program A’s student and 100% in program B. As many as (91.8%) A program’s students and (100%) B program’s students were good enough on the used of double gloves. Conclusion: In generally nursing profession students did not realized that importance of needle stick prevention, therefore majority of students were good enough on needle stick injury prevention. This study can be a refference for educational institution to provide training that related to prevention of needle stick injury before professional practice. Keywords: Prevention, Needle Stick Injury, Nursing Proffesion Students